Preemptive use of Small Dose Fentanyl Suppresses Fentanyl Induced Cough - Shrestha, SK; Bhattarai, B; Shah, RS (Kathmandu University Medical Journal, 2014)
Background Fentanyl, a synthetic opioid, is a popular choice amongst anaesthesiologists in the operating room. Pre induction intravenous fentanyl bolus is associated with coughing in 28 – 65% of patients. Fentanyl induced cough is not always benign and can be remarkably troublesome at the most critical moment of anaesthesia when airway reflex is lost. Objectives To study the effect of pre emptive use of minimal dose fentanyl through the peripheral venous cannulae on the incidence of cough by a larger bolus of intravenous fentanyl. Methods One hundred and fifty patients aged 18 -75 years undergoing elective surgical procedures were randomized into three groups of 50 each. The first group received 0.5 ml saline 0.9 % intravenously one minute prior to the administration of fentanyl 150μg (3 ml); the second group received pre emptive fentanyl 25μg(0.5ml) prior to the administration of fentanyl 125μg(2.5ml); and the third group received preemptive fentanyl 25 μg(0.5ml), followed by the administration of fentanyl 150μg(3ml).. Based on the number of coughs observed, cough severity was graded as mild(1-2), moderate (3-5),or severe (>5). Results The incidence of fentanyl induced cough was significantly lower in both pre emptive group 4(8%) for 125μg fentanyl and 7(14%) for 150μg than in the saline group 15(30%). Conclusion Pre- emptive use of minimal dose fentanyl 25μg administered one minute before a larger bolus dose of fentanyl (125 or 150μg ) can effectively suppress cough. DOI: http://dx.doi.org/10.3126/kumj.v10i4.10988 Kathmandu Univ Med J 2012;10(4):16-19